Uma introdução à curvas planas - Gomes, Anderson de Azevedo (2015)
Beginning with the concept plan and how it can be represented in a Vector Plan. Show the identity of vectors and the basic properties of the vector sum with examples and continue with the properties of the Scalar product and how to nd the Angle Between Vectors. After we nd the projection vectors and the distance between a point and a Straight. In the next chapter, I review on Conic Sections. Tract of Ellipse, after Hyperbole and analyze talking about the parable and its utilities. In sequence, show the Parametric equations of a curve. Come to a formula of how to nd a tangent vector and how to nd the length of an arc. Show the usefulness of the Frenet formulas and do the Fundamental Theorem of Plane Curves and their utilities. To end tract Importance of Mathematics in Primary Education with a little history of Dynamic Geometry Software and Software Geogebra, showing how to make some charts in GeoGebra. My goal is to show the beauty of mathematics and attract people to the area.